2017
DOI: 10.22159/ajpcr.2017.v10i3.16378
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Lantana Camara Linn.

Abstract: Herbal drugs are the potential sources of therapeutic aid for the treatment and prevention of number of ailments as recognized very early by Ayurveda, Unani, and traditional folk -medical practitioners. The rich biodiversity of plants makes them a treasure house for obtaining new and novel compounds either themselves as drugs or lead molecules for drugs with different mechanisms of action. Lantana camara L. belonging to the family Verbenaceae and universally known as wild or red sage is the most widespread spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…It is used as a sudorific, intestinal antiseptic, diaphoretic, and in treatment of tetanus and rheumatism and malaria in Indian medicine (Ojha & Dayal, 1992). Extracts from the leaves exhibit antimicrobial, fungicidal, insecticidal and nematicidal activity (Begum et al, 2000;Day et al, 2003;Girish, 2017). It is useful for fistulae, pustule and tumours.…”
Section: Herbal Medicinementioning
confidence: 99%
“…It is used as a sudorific, intestinal antiseptic, diaphoretic, and in treatment of tetanus and rheumatism and malaria in Indian medicine (Ojha & Dayal, 1992). Extracts from the leaves exhibit antimicrobial, fungicidal, insecticidal and nematicidal activity (Begum et al, 2000;Day et al, 2003;Girish, 2017). It is useful for fistulae, pustule and tumours.…”
Section: Herbal Medicinementioning
confidence: 99%
“…Many authors have mentioned the secondary metabolites of extract effective against micro organism were evaluated and recognized as saponins, tannins, cardiac glycosides, alkaloid, flavonides, steroids, terpenoids 19 . However, most of pharmacological studies were preliminary and require intensive preclinical and clinical studies to evaluate the efficacy and toxicity of these plant products 20 . The results of this experimental study showed that the effectiveness of extracts was dependent of concentration used, thus increase in extract concentration leads to increase the inhibition zone.…”
Section: Test Bacterial Strainmentioning
confidence: 99%
“…Lanatana camara L., family Verbenaceae, the reported secondary metabolites are terpens, iridoid glycosides, furanonaphthoquinones, flavonoids, and phenylethanoid glycosides [7]. Lantana camara L. has broad antibacterial, antifungal, antiviral, and antiparasitic activities [7,8]. Myrtus communis L. family Myrtaceae has been used in traditional medicines for the treatment of lung disorders and rich in phenolic acids, flavonoids, tannins, volatile oils and fatty acids.…”
Section: Introductionmentioning
confidence: 99%